2023
DOI: 10.5194/essd-2023-65
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subsurface geological and geophysical data from the Po Plain and the northern Adriatic Sea (north Italy)

Abstract: Abstract. The Po Plain (Italy) is one of the most densely populated and productive regions of Europe, characterized by a flourishing economy (also linked to strategic subsurface resources) and several world cultural and natural heritage sites. The coupling of social-economic interests with geological hazards (i.e., seismic, subsidence and flooding hazards) in this area requires accurate knowledge of the subsurface geology, active geological processes, and impact of human activities on natural environments to m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The San Giorgio parish church is located in Northern Italy, a few kilometers from Argenta, a small town in Emilia-Romagna, not far from the sea (Figure 1). The Emilia-Romagna plain, in which Argenta is located, is the result of the filling of the Padano Perisutural Basin, a vast depression delimited by the Apennine and Alpine reliefs, which occurred through a powerful accumulation of marine and alluvial deposits from the Pliocene and Quaternary ages [Pieri and Groppi, 1981;Livani et al, 2023]. The subsoil of the municipal territory of Argenta is made up of non-lithified alluvial and deltaic plain sediments with a thickness of several hundred meters.…”
Section: Historical and Archaeological Data In Geological Frameworkmentioning
confidence: 99%
“…The San Giorgio parish church is located in Northern Italy, a few kilometers from Argenta, a small town in Emilia-Romagna, not far from the sea (Figure 1). The Emilia-Romagna plain, in which Argenta is located, is the result of the filling of the Padano Perisutural Basin, a vast depression delimited by the Apennine and Alpine reliefs, which occurred through a powerful accumulation of marine and alluvial deposits from the Pliocene and Quaternary ages [Pieri and Groppi, 1981;Livani et al, 2023]. The subsoil of the municipal territory of Argenta is made up of non-lithified alluvial and deltaic plain sediments with a thickness of several hundred meters.…”
Section: Historical and Archaeological Data In Geological Frameworkmentioning
confidence: 99%
“…The available data from the well profiles were collected, digitized, and analyzed in previous works [44,45]. Benetatos et al [44] were able to group the identified lithologies into nine lithological groups (six clastic, one marly, and two carbonatic).…”
Section: Validation Of the Geomechanical Simulationsmentioning
confidence: 99%
“…Primitive and derived data are available for open access in ASCII format at the following link: https://doi.org/10.5281/zenodo.8126519 (Livani et al, 2023). The format and the organization of data are explained in the related description file.…”
Section: Data Availabilitymentioning
confidence: 99%
“…Nowadays, such issues are particularly relevant for the underground industry development related to the increasing interest in possible CO 2 and hydrogen underground storage, which can play a fundamental role in the energy transition process towards decarbonization goals. The full dataset is available at the following link: https://doi.org/10.5281/zenodo.8126519 (Livani et al, 2023).…”
mentioning
confidence: 99%